2022
DOI: 10.3389/fpubh.2021.814208
|View full text |Cite
|
Sign up to set email alerts
|

Nexus Between Foreign Direct Investment Inflow, Renewable Energy Consumption, Ambient Air Pollution, and Human Mortality: A Public Health Perspective From Non-linear ARDL Approach

Abstract: A huge foreign direct investment (FDI) inflow has been witnessed in China, though on the one hand, it brings a significant contribution to economic growth. On the other hand, it adversely affects the ambient air pollution that may affect human mortality in the country. Renewable energy (RE) usage meets the country's energy needs with no adverse effect on the environment. Therefore, this study is trying to empirically analyze the effect of FDI inflow on human morality and RE consumption in China. We used time-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 57 publications
3
25
0
Order By: Relevance
“…These countries prioritize achieving their goals of economic expansion and energy independence over protecting the environment ( 88 ). In addition, our findings are consistent with the research that is already published, such as a study that was conducted in 31 provinces in China ( 37 ), a study that was conducted in the United States of America that also supports the frequency of inverted u-shaped ENVIRONMENT KUZNETS CURVE ( 12 ), and a study that suggests the same results as Shahbaz et al (2019), the study of Shah et al, ( 85 ), a case study that was conducted by Fu et al ( 89 ), Shah et al ( 87 ) and Shah et al ( 85 ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These countries prioritize achieving their goals of economic expansion and energy independence over protecting the environment ( 88 ). In addition, our findings are consistent with the research that is already published, such as a study that was conducted in 31 provinces in China ( 37 ), a study that was conducted in the United States of America that also supports the frequency of inverted u-shaped ENVIRONMENT KUZNETS CURVE ( 12 ), and a study that suggests the same results as Shahbaz et al (2019), the study of Shah et al, ( 85 ), a case study that was conducted by Fu et al ( 89 ), Shah et al ( 87 ) and Shah et al ( 85 ).…”
Section: Resultssupporting
confidence: 92%
“…The findings of the study are in line with what was expected ( 7 ). However, the findings that we obtained from this research are more solid and trustworthy than others because we utilized estimation strategies that account for heterogeneity ( 85 ).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Their findings showed the growth of renewable energy use and its impact on other social aspects, rather than the existence of causal linkages between health and renewable energy. Shah et al ( 26 ) analyzed the FDI inflow, mortality and renewable energy consumption in China for the period 1998–2020. They reported that a significant amount of FDI inflow had occurred in the last few decades.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Environmental science documented that economic progress and development at a large-scale lead to the depletion of earth resources, increasing the levels of air/water/land pollution, loss of biodiversity, and extreme climate temperatures (Polasky et al, 2019). These ecological changes have an inverse impact on the human well-being and the quality of the environment (Sandifer et al, 2015;Shah et al, 2022). In this respect, several domestic and international institutions consider rising carbon emissions and climate change the most pressing issues (IPCC, 2020).…”
Section: Introductionmentioning
confidence: 99%